Higher generating subgroups and Cohen–Macaulay complexes. Issue 1 (17th February 2020) - Brück, Benjamin
Abstract: We show how to find higher generating families of subgroups, in the sense of Abels and Holz, for groups acting on Cohen–Macaulay complexes. We apply this to groups with a BN-pair to prove higher generation by parabolic and Levi subgroups and describe higher generating families of parabolic subgroups in Aut( F n ).